Barriers to access and minority ethnic carers' satisfaction with social care services in the community: a systematic review of qualitative and quantitative literature. (19th August 2014) - Greenwood, Nan; Habibi, Ruth; Smith, Raymond; Manthorpe, Jill
Abstract As populations age, the numbers of carers overall and numbers of carers from minority ethnic groups in particular are rising. Evidence suggests that carers from all sections of the community and particularly carers from minority groups often fail to access care services. This may relate to barriers in accessing services and service dissatisfaction. The aim of this systematic review was to identify and summarise minority ethnic carers' perceptions of barriers to accessing community social care services and their satisfaction with these services if accessed. The following databases were searched from their start until July 2013: Social Care Online, Social Policy and Research, Scopus, PsychINFO, HMIC, ASSIA, MEDLINE, Embase, CINAHL Plus and AMED. Thirteen studies met the inclusion criteria. Most investigated either barriers to access or satisfaction levels, although three explored both. Only 4 studies investigated minority ethnic carers' satisfaction with social care, although 12 studies reported perceived barriers to accessing services. Few studies compared minority ethnic carers' perceptions with majority ethnic groups, making it difficult to identify issues specific to minority groups. Most barriers described were potentially relevant to all carers, irrespective of ethnic group. They included attitudinal barriers such as not wanting to involve outsiders or not seeing the need for services and practical barriers such as low awareness of services and service availability. Issues specific to minority ethnic groups included language barriers and concerns about services' cultural or religious appropriateness. Studies investigating satisfaction with services reported a mixture of satisfaction and dissatisfaction. Barriers common to all groups should not be underestimated and a better understanding of the relationship between perceived barriers to accessing services and dissatisfaction with services is needed before the experiences of all carers can be improved.